2019
DOI: 10.1007/s12630-019-01372-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between incremental remifentanil doses and the Nociception Level (NOL) index response after intraoperative noxious stimuli

Abstract: Background The Pain Monitoring Device (PMD) monitor (Medasense Biometrics Ltd., Ramat Gan, Israel) uses the Nociception Level (NOL) index, a multiple parameterderived index that has recently shown a good sensitivity and specificity to detect noxious stimuli. The aim of this study was to assess the latest version of the device (PMD200 TM) on variations of the NOL response after standardized tetanic stimuli to study the correlation between remifentanil doses and NOL. Methods Data from 26 patients undergoing midl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 37 publications
3
39
0
3
Order By: Relevance
“…The NOL monitoring allowed us to titrate the amount of opioid that we used during the non-stimulating phases of the surgery. 19 Finally, the synchronization of the two different surgeries was very important to reduce the ischemic time of the graft to a minimum and to allow the other organs of the donor to be procured in an optimal time. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NOL monitoring allowed us to titrate the amount of opioid that we used during the non-stimulating phases of the surgery. 19 Finally, the synchronization of the two different surgeries was very important to reduce the ischemic time of the graft to a minimum and to allow the other organs of the donor to be procured in an optimal time. 20…”
Section: Discussionmentioning
confidence: 99%
“…The NOL monitoring allowed us to titrate the amount of opioid that we used during the non-stimulating phases of the surgery. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In our proposed study, remifentanil infusion will be guided in both groups on a nociception index, the NOL index. The NOL index is a tested and validated measure that shows a high correlation between pain measurements and doses of intraoperative opioids and is commonly used in our center at Maisonneuve-Rosemont Hospital / CEMTL [ 38 , 39 ]. Moreover, mean blood pressure targets will be personalized, and cerebral oximetry monitoring used to ensure comparability of the two groups regarding intraoperative hemodynamic management.…”
Section: Discussionmentioning
confidence: 99%
“…Although different study protocols have been proposed to examine the correlation between measures and balance of NAN, for example, some researchers [25] [27] applied tetanic stimulus at varying concentrations of remifentanil in one person whereas Bonhomme et al [28] , Rantanen et al [29] , and our study assigned patients to several groups and observed the response of each patient to intraoperative stimulation at only one target concentration of analgesics, the essence of study design is identical, that is, keeping hypnotic level and nociception level constant when altering the level of analgesia. It is well known that general anesthesia is mainly consisted of hypnosis and analgesia; therefore, the prerequisite for analyzing analgesia during general anesthesia is to adjust the level of hypnosis to an adequate and appropriate state.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the discarded data (−10 to +10 s) could separate the data before and after the event clearly without losing the crucial information generated by stimulus. Both maximum and average value have been used to describe the reactions to stimulus [25] [28] . Maximum could preferably characterize some salient features which increase with the existence of noxious event, but it is vulnerable to outliers and could not explain the decreased features felicitously.…”
Section: Discussionmentioning
confidence: 99%